2021
DOI: 10.31124/advance.13516769
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lawyers Response to COVID-19 Infodemic on Social Media

Abstract: <p><b>Objectives</b>: The primary objective of this study is to examine and analyze the skills and practices of lawyers in response to the misinformation/Infodemic of COVID-19 on Social Media platforms.</p> <p><b>Research Methodology</b>: In this quantitative study an online survey was conducted among lawyers in Pakistan. The population of the study was made up of practicing lawyers from different District Bar Associations in Pakistan. A questionnaire was distributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, immediate and mass delivery of information is a major advantage of newspapers. Moreover, Jamshed 20 contends that the information on COVID-19 in newspapers is more reliable than that in social media.…”
Section: Introductionmentioning
confidence: 99%
“…However, immediate and mass delivery of information is a major advantage of newspapers. Moreover, Jamshed 20 contends that the information on COVID-19 in newspapers is more reliable than that in social media.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings showed that the surface heat transfer rate increases the volume fraction of nanomaterials. Entropy generation has been measured by Jamshed (2021) in the MHD flow of Maxwell nanofluid that passes infinite horizontal sheets in terms of the imposed viscous dissipation and thermal radiation effects. Many researchers have been paying close attention to the study of nanofluid flow through porous surfaces, and Henry Darcy's 1856 Darcy model is the most used model in this kind of study (Darcy, 1965).…”
Section: Introductionmentioning
confidence: 99%